Overview of Work Readiness in Industrial Practice Students - Novita Maulidya Jalal (MultiTech Publisher, 2023)
The aim of this research is to determine the picture of work readiness of students who practice in industry. The method in this research is a literature study with descriptive methods. The journals used in this research consisted of 7 journals with similar research themes, namely student work readiness and industrial practice. The results obtained in this research are that students are more ready to work after carrying out industrial practice because students gain experience to develop skills according to their field of expertise, and students are better able to adapt to new environments. The implication of this research is to provide knowledge regarding the description of work readiness for students who practice in industry.